Implikasi Pedagogis dari Q.S. Al-Ahzab Ayat 45-47 terhadap Pokok dan Fungsi Pendidik - Milleandi Indra Regina (UPT Publikasi Ilmiah Unisba, 2023)
Abstract. Teachers are educators, namely anyone who strives for the development of all the potential of students, both psychomotor and cognitive potentials. The teacher is also a bridge between progress and the abyss of civilization destruction, it depends on the teacher's task, the teacher who knows his duties, and can carry it out well, can be a bridge to the progress of civilization, but if the teacher does not know or even ignore his duties as a teacher, then it can become the brink of collapse of civilization, which will lead to the loss of commendable behavior and achievements for students, society and even civilization.The purpose of this research is to find out: 1). The opinion of the commentators about the QS. Al-Ahzab verses 45-47, 2). Pedagogical implications of QS. Al-Ahzab verses 45-47, 3). analysis of Islamic Education about QS. Al-Ahzab verses 45-47 on the teacher's duties. This research departs from the thoughts of the researcher, that education is something that is always seen wherever it is, because if the education is good, the future of the nation will also be good, and if the education is bad, the future of the nation will also be bad, but education will never be separated. with the teacher, because it is the teacher who provides teaching and also experience to students or students, but good and successful students will not be created if the teacher is not good and does not know their duties well. This study uses a qualitative research approach with library research data collection techniques (library research) with primary data sources including: Tafsir Ibn Kathir, Tafsir Jalalain, Tafsir Al-Azhar, Tafsir Al Qurthubi and Tafsir Al-Mishbah. While the secondary sources are supporting books related to research problems, including books on Islamic Education and others. The data obtained were then analyzed through a unit process, categorization, data interpretation, and drawing conclusions. The results of this study are: 1). The opinion of the commentators about the QS. Al-Ahzab verses 45-47 are not much different from each other. This is proven when the commentators interpret the word